Tata Kelola Sistem Informasi Distribusi Rekam Medis Rawat Jalan Di Puskesmas Linggar Rancaekek - Rosidah, Nida; sufyana, Candra mecca; suryani, Ade irma (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2024)
The activity of distributing medical record at the Linggar Health Center, Rancaekek is still being carried out manually by officers and recorded in the expedition book. So that problems arise, namely the lack of time efficiency because officers need more time and experience delays in processing data on distributing medical record files. Based on these findings, the authors designed an information system for the distribution of medical record files that could maximize the performance of officers so that officers were expected to be able to provide improved quality of service to patients. The method used in this research is a qualitative method, where the measurement of this research is not based on scores/numbers, but on the category of value or quality. Data collection techniques were carried out using direct observation, interviews with a total sample of 3 medical record officers, and a literature review. The stages of collecting data are carried out by direct observation of the research site. In the development method, using the waterfall method. Analysis of the needs of this design system is made through the stages of context diagrams, Data Flow Diagrams (DFD), and Entity Relationship Diagrams (ERD).